Αppendix B - The Ancient Guitar Project / Αppendix B - The Ancient Guitar Project - Πολίτης Διονύσιος (ΑΡΙΣΤΟΤΕΛΕΙΟ ΠΑΝΕΠΙΣΤΗΜΙΟ ΘΕΣΣΑΛΟΝΙΚΗΣ, 2016)
Αppendix B - The Ancient Guitar Project: Μουσική Μουσική Μουσική Μουσική Ο invited member of the ancient Greek hit are in our face. This interface teaches you how to know how the notes, on the ancient, were read or played and sounded. You have three options in the way of playing a note. You can press a button in the name of a note, and then press play button to hear it. You can select the note using. Υπότιτλοι AUTHORWAVE